B-Z junctions in supercoiled pRW751 DNA contain unpaired bases or non-Watson-Crick base pairs - Palecek, E; Boubliková, P; Nejedlý, K; Galazka, G; Klysik, J (Journal of biomolecular structure & dynamics, 1987)
Structural distortions on the boundary between right-handed and left-handed DNA segments in negatively supercoiled plasmid pRW751 (a derivative of pBR322 containing (dC-dG)13 and (dC-dG)16 segments) were studied by means of osmium tetroxide, pyridine and glyoxal. These two probes react preferentially with single-stranded DNA, but only the latter requires non-paired bases for the reaction. Nuclease S1 and testing of the inhibition of BamHI cleavage (whose recognition sequences GGATCC lie on the "outer" boundaries between the (dC-dG)n and the pBR322 nucleotide sequence) were used to detect the site-specific chemical modification in pRW751. As a result of glyoxal treatment BamHI cleavage was strongly inhibited in topoisomeric samples whose superhelical density was sufficiently negative to stabilize the (dC-dG)n segments in the left-handed form. Osmium tetroxide, pyridine modification resulted in a similar inhibition of BamHI cleavage and in a formation of nuclease S1 sensitive sites. The results suggest that the "outer" B-Z junctions in pRW751 contain one or few non-paired bases or non-Watson-Crick base pairs.
Keywords: pyridiny; Base Sequence; oxid osmičelý; Single-Strand Specific DNA and RNA Endonucleases; glyoxal; DNA, Superhelical; rekombinantní DNA; DNA; Nucleic Acid Conformation; zastoupení bazí; deoxyribonukleasa BamHI; konformace nukleové kyseliny; superhelikální DNA; Glyoxal; plazmidy; Osmium Tetroxide; Pyridines; Base Composition; sekvence nukleotidů; Deoxyribonuclease BamHI; Plasmids; DNA, Recombinant; endonukleasy specifické pro jednořetězcové nukleové kyseliny